Multilevel Analysis on the Biosocial and Economic Determinants of Exclusive Breastfeeding - Sinta, Prabawati; Salimo, Harsono; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2018)
Background: Exclusive breastfeeding is provided to infants from birth to 6 months of age without supplementary or substitution food and drink. Breastmilk contains nutrients and protective factors that can reduce morbidity and mortality risks of children. This study aimed to determine the effect of maternal nutritional status, parity, employment status, family income, health personnel support, subjective norm, and stratification status of community health center (posyandu), on exclusive breastfeeding in Banjarsari Sub-District, Surakarta. Subjects and Method: This was an analytic observational study with cross sectional design. The study was conducted in Banjarsari sub-district, Surakarta, Central Java, from October 17 to November 7, 2017. Twenty five posyandus were selected by stratified random sampling. Of the posyandus selected, 200 lactating mothers were selected by simple random sampling. The dependent variable was exclusive breastfeeding. The independent variables were maternal nutritional status, parity, employment status, family income, subjective norm, and health personnel support. The data were collected using a set of questionnaire and analyzed by multilevel logistic regression in Stata 13. Results: The likelihood of exclusive breastfeeding increased with better maternal nutritional status (b= 1.65; 95% CI= 0.14 to 3.17; p= 0.032), multi parity (b= 1.72; 95% CI= 0.57 to 2.86; p= 0.003), working outside the house (b= -2.94; 95% CI= -3.99 to -1.88; p= 0.001), higher family income (b= -1.94; 95% CI= -3.13 to -0.76; p= 0.001), strong health personnel support (b= 1.13; 95% CI= 0.02 to 2.25; p= 0.046), and positive subjective norm (b= 1.20; 95% CI= 0.14 to 2.25; p= 0.025). Posyandu showed strong contextual effect on exclusive breastfeeding with intra-class correlation (ICC)= 28.87%. Conclusion: The likelihood of exclusive breastfeeding increases with better maternal nutritional status, multi parity, working outside the house, higher family income, strong health personnel support, and positive subjective norm. Keyword: exclusive breastfeeding, multilevel analysis, maternal nutritional status, parity, employment status, family income, health personnel support, subjective norm, and posyandu Correspondence: